The Implementation of Using Small Goup Discussion in an EFL Classroom: (A Case Study at the Eleventh Grade of SMKN 1 Subang in the Academic Year 2022/2023) - Ika Sapitri; Mimin Aminah; Muhammad Anjar Nugraha (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2024)
Students have difficulty learning English because they do not use it in their daily lives and English is not their first language. Through small group discussion as a learning strategy can help students’ in learning English. This study, focused on a described implementation of using small group discussion in an EFL classroom and perceived students’ responses about this strategy. This case study was conducted at Vocational High School, consists of 34 students and was designed for two meetings with the material analytical exposition text. To triangulate the data, observation, questionnaire, interview and documentation were used as an instrument. The result shows that implementation by group discussion the students more easily to analyze and makes an analytical exposition given by the researcher. Although in the first meeting, there were students who did not seem to participate in the process of discussion, but in second meeting, students participated actively and they could manage themselves to work in-group. In the questionnaire, 100% of students agree that using small group discussion is very suitable for learning English in vocational school. Based on the interview, students argue that by small group discussion it can be solved the task easily because they have the various opinions during group discussion. Small Group Discussion really helped the students. The students could share their knowledge and opinion in doing the exercises and discussing the answer to the exercises. Based on the result, it can be concluded that implementing small group discussion as a learning strategy is a good way of teaching and learning English.